Palaemonidae, Euryrhynchidae, and Sergestidae (Crustacea: Decapoda): Records of native species from the states of Amapá and Pará, Brazil, with maps of geographic distribution - Pimentel, Fabiana Ribeiro; Magalhães, Célio (Check List, 2014)
A list of the distribution records for 18 species of freshwater shrimps of the families Euryrhynchidae (3 spp.), Palaemonidae (13 spp.) and Sergestidae (2 spp.) from the states of Amapá and Pará are presented. All records are documented by voucher specimens deposited in the three main carcinological collections from northern Brazil: Instituto de Pesquisas Científicas e Tecnológicas do Amapá (Macapá), Instituto Nacional de Pesquisas da Amazônia (Manaus), and Museu Paraense Emílio Goeldi (Belém). Maps of the geographic distribution of these records in the eastern Amazon region are offered, and comments on the zoogeography of the species are made. © 2014 Check List and Authors.